STRATEGI PEREMPUAN DALAM KEMANDIRIAN GIZI KELUARGA (Studi Kelompok Pengajian Putri Nurul Hidayah Blabak Kota Kediri) - Diah Handayani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This study trying to analized the implementation of social empowerment programme as the women organization to keep the family nutrition. Nutrient balance behaviour is a knowledge, behaviour, and family about nutients in Blabak, Pesantren, Kediri. The aim of this activities is to make family able to prevent bad nutrient status and increasing nutrient status of the children. And increasing role of the women in rural areas to make the stabilization of the system by increasing the resilence of families and function empowerment and family welfare movementby the non formal organization. Also the Pengajian Nurul Hidayah strenghtening the functions and performance in order posyandu primary health care for infants and mothers. Facilitating the cooperation of the women to earn the money for providing food companion toddler feeding.